Risk factors for periorbital dermatitis in patients using dorzolamide/timolol eye drops - Myungjin Kim; Hyoju Jang; Seungsoo Rho (Scientific Reports, 2021)
Abstract This study assessed the clinical risk factors for periorbital dermatitis (PD) after using dorzolamide/timolol eye drops in a total of 1282 glaucoma patients. Both the PD(+) group and the PD(−) group were evaluated using clinical data such as age, sex, dosing duration, presence of benzalkonium chloride (BAK) in the formulation, ocular surgery history (e.g. cataract or glaucoma operations), height, weight, personal history of systemic hypertension, smoking, alcohol consumption, intraocular pressure, best-corrected visual acuity (BCVA), central corneal thickness, axial length, and visual field index (VFI). Univariate analyses showed that shorter dosing duration, higher rate of BAK-included cases, worse BCVA, worse VFI, more systemic hypertension history, and more ocular surgery history were more associated with the PD(+) group than the PD(−) group. The BAK(−) group showed a lower PD rate than the BAK-included group, which was supported by the Kaplan–Meier analysis (log-rank test, p = 0.0014). Multivariate analyses revealed that the probability of PD increased by 8 times if they had a history of ocular surgery and increased by 2.3% when the VFI decreased by 1% (Cox’s hazard regression test, p < 0.001). Therefore, a preservative-free dorzolamide/timolol can benefit the subjects for those who had ocular surgery or who have worse VFI.